The Impact of Managerial Capabilities on the Effectiveness of Sustainable Economic Development: A Systematic Literature Review - Ahmad Firdaus; Lina Mariana (Pustaka Digital Indonesia, 2026)
Sustainable economic development has become a critical global priority, requiring organizations to balance economic growth with environmental sustainability and social equity. This study aims to examine the impact of managerial capabilities on the effectiveness of sustainable economic development through a systematic literature review. Using the PRISMA framework, this research analyzes 52 peer-reviewed articles published between 2021 and 2025, sourced from major academic databases including Scopus, Web of Science, ScienceDirect, and SpringerLink. The findings reveal that managerial capabilities—encompassing strategic decision-making, leadership, innovation management, and adaptability—play a central role in driving sustainability outcomes. These capabilities enable organizations to align business strategies with sustainability goals, optimize resource utilization, and respond effectively to dynamic environmental challenges. The study further identifies innovation as a key mediating variable that translates managerial competencies into sustainable performance, while leadership and organizational culture act as moderating factors that strengthen this relationship. Additionally, digital transformation emerges as a critical enabler that enhances managerial effectiveness by improving decision-making, operational efficiency, and organizational agility. The results also highlight that managerial capabilities are particularly crucial in emerging economies, where institutional limitations and resource constraints demand adaptive and innovative approaches. This study contributes to the literature by integrating multiple theoretical perspectives and proposing a comprehensive framework linking managerial capabilities to sustainable economic development. The findings provide important implications for managers, policymakers, and researchers in advancing sustainability-oriented strategies.